Erythromelanosis follicularis faciei et colli: A first female case report from the outskirts of Libya and literature review - Ebtisam Elghblawi (Wolters Kluwer Medknow Publications, 2017)
Erythromelanosis follicularis faciei (EFF) is a rare sporadic condition of unclear etiology and is distinctive by well-demarcated reddish-brown patches and follicular papules that appear often on the face and seldom on the neck. Herein, I report a case of a 15-year-old female who had asymptomatic facial skin discoloration since early childhood. Skin examination revealed confluent nonscaly rough brownish red patches on both cheeks without telangiectasia and a barely thick scaly brownish patch over her entire forehead and both eyebrows with follicular plugging. A summary of preceding reports of EFF in the literature is presented in this report.